The utility of the International Classification of Functioning, Disability and Health: Versions for children and youth (ICF-CY) in early intervention and special education contexts - Rosário, Helena (2009)
This paper discusses the utility of the International Classification of Functioning, Disability and Health – Children and Youth – ICF-CY (WHO, 2007) in the scope of Early Intervention and Early Childhood Special Education. We will discuss the relevance of the ICF- CY as an operationalization of an unifying and comprehensive theoretical approach. This approach describes the person’s functioning while taking into account individual participation, based in an interactive person-environment process, thus overcoming the diagnostic approaches to development. The general lines of research that are being developed at the  Faculdade de Psicologia e de Ciências da Educação da Universidade do Porto, concerning the utility of the classification in the assessment-intervention process in Early Intervention and Early Childhood Special Education will be presented.  DOI: http://dx.doi.org/10.17575/rpsicol.v23i2.332